An overview of burst, buckling, durability and corrosion analysis of lightweight FRP composite pipes and their applicability. (15th December 2019) - Manoj Prabhakar, M.; Rajini, N.; Ayrilmis, Nadir; Mayandi, K.; Siengchin, Suchart; Senthilkumar, K.; Karthikeyan, S.; Ismail, Sikiru O.
Abstract: The main aim of this review article was to address the performance of filament wound fibre reinforced polymer (FRP) composite pipes and their critical properties, such as burst, buckling, durability and corrosion. The importance of process parameters concerning merits and demerits of the manufacturing methods was discussed for the better-quality performance. Burst analysis revealed that the winding angle of ±55° was observed to be optimum with minimum failure mechanisms, such as matrix cracking, whitening, leakage and fracture. The reduction of buckling effect was reported in case of lower hoop stress value in the hoop to axial stress ratio against axial, compression and torsion. A significant improvement in energy absorption was observed in the hybrid composite pipes with the effect of thermal treatment. However, the varying winding angle in FRP pipe fabrication was reported as an influencing factor affecting all the aforementioned properties. Almost 90% of the reviewed studies was done using E-glass/epoxy materials for the composite pipe production. By overcoming associated limitations, such as replacing synthetic materials, designing new material combinations and cost-benefit analysis, the production cost of the lightweight FRP composite pipes can be decreased for the real-time applications.